The Effect of Education on The Level of Knowledge and Readiness to Provide Basic Life Support to 12th Grade Students of SMK Muhammadiyah 2 Tegal City - Sucipto, Rizqi Azril; Sunaryo, Aris; Sulistiyana, Catur Setiya (Syntax Literate, 2025)
Basic life support is the first aid action to help victims with emergency conditions, generally the knowledge of ordinary people and students about basic life support is still relatively low. Objective: To determine the effect of education on the level of knowledge and readiness to provide Basic Life Support to 12th grade students of SMK Muhammadiyah 2 Tegal City. Method: This study used quasi experimental method with one group post-test only. The measuring instrument used in this study was a questionnaire with 92 students as respondents. Results: Based on the results of the study after giving education about BHD obtained, the level of knowledge of respondents in the good category as many as 65 respondents (71%) and in the category less as many as 19 respondents (20%). The level of readiness of respondents in the ready category was 46 respondents (50%) and very ready as many as 14 respondents (15%). Conclusion: The effect of education on the level of knowledge in students gives positive results, namely in the good category. And for the effect of education on student readiness to provide basic life support is in the ready category.